THE INFLUENCE OF WORK MOTIVATION AND WORK ETHIC ON EMPLOYEE WORK PRODUCTIVITY IN THE WAREHOUSE RECEIPT SYSTEM AND COMMODITY AUCTION MARKET GUIDANCE AND DEVELOPMENT DIVISION OF THE COMMODITY FUTURES TRADING SUPERVISORY AGENCY (BAPPEBTI) OFFICE - Arifudin Akbar; Zulkifli Rangkuti; Jamal Hanaffy (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to determine the effect of motivation and work ethic on work productivity at the Office of Warehouse Receipt System Development and Commodity Auction Market Office of the Commodity Futures Trading Regulatory Agency (BAPPEBTI). The phenomenon underlying this study is the discovery of employees with a level of work productivity that is not optimal. In this study the author used quantitative research. The population in this study was 145 employees. In this study the author used a sampling technique using the Slovin formula for 59 people. Data were collected using a closed questionnaire with a Likert scale, and analyzed using multiple linear regression with the help of the SPSS program version 20. The results of the study indicate that partially and simultaneously, the influence of motivation and work ethic has a positive and significant effect on work productivity. This study emphasizes the importance of being able to follow up with appropriate policies in order to be able to increase work productivity optimally.